Integrated U–Pb, Lu–Hf and (U–Th)/He analysis of zircon from the Banxi Sb deposit and its implications for the low-temperature mineralization in South China - Li, H.; Danišík, Martin; Zhou, Z.K.; Jiang, W.C.; Wu, J.H. (CHINA UNIV GEOSCIENCES, BEIJING, 2020)
Low-temperature Sb (Au–Hg) deposits in South China account for more than 50% of the world's Sb reserves, however, their genesis remains controversial. Here we report the first study that integrates U–Pb and Lu–Hf analysis by LA-(MC)-ICPMS and conventional (U–Th)/He analysis, all applied to single zircon crystals, in an attempt to constrain the origin and timing of world-class Sb (Au–Hg) deposits in Banxi (South China). Zircon separated from a quartz-stibnite ore and an altered country rock samples revealed similar U–Pb age spectra defining two major populations – Paleoproterozoic (~1900–2500 ​Ma) and Neoproterozoic (~770 ​Ma), which are characterized by variable εHf(t) values (–10.7 to 9.1 and –16.5 to 11.2, respectively) and Hf crustal model ages (TDMC) (2.48 to 3.24 ​Ga and 0.97 to 2.71 ​Ga, respectively). The U–Pb age and Hf isotopic features of the zircons are consistent with the Banxi Group in the region, indicating that the zircons involved in the low-temperature hydrothermal system were originally from the Banxi Group country rocks. Thirty-three mineralization-related zircon crystals yielded a mean (U–Th)/He age of 123.8 ​± ​3.8 ​Ma, which is interpreted to represent the timing of the latest low-temperature mineralization stage of the Banxi Sb deposit. The combined U–Pb, Lu–Hf and (U–Th)/He data suggest that Precambrian basement rocks were the major contributors to the low-temperature mineralization, and that Early Cretaceous (130–120 ​Ma) could be the most important ore-forming epoch for the Sb deposits in South China. This study also demonstrates the analytical feasibility of integrated U–Pb - Lu–Hf - (U–Th)/He “triple-dating”, all applied to single zircon crystals. This approach reveals the full evolution of zircon, from its origin of the magmatic source, through its crystallization and low-temperature cooling. Although this study demonstrates the usefulness of this integrated approach in dating low-temperature mineralization, it has great potential for zircon provenance and other studies that may benefit from the large amount of information that can be extracted from single zircon crystals.